2012
DOI: 10.1177/1087057112449864
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Appropriate Stage of Human-Induced Pluripotent Stem Cell–Derived Cardiomyocytes for Drug Screening and Pharmacological Evaluation In Vitro

Abstract: Human-induced pluripotent stem cell-derived cardiomyocytes (hiPS-CMs) at different stages (approximate days 30, 60, and 90) were used to determine the appropriate stage for functional and morphological assessment of drug effects in vitro. The hiPS-CMs had spontaneous beating activity, and β-adrenergic function was comparable in all stages of differentiation. Microelectrode array analyses using ion channel blockers indicated that the electrophysiological properties of these ion channels were comparable at all d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 31 publications
2
19
0
Order By: Relevance
“…Furthermore, we found that the average beat frequency of hiPSC-CMs on microposts coated with all three ECM proteins was approximately equal, and only varied from 0.9 to 1.1 Hz. These findings agree with previous measurements of the spontaneous beating rate for early-stage iPSC-derived cardiomyocytes, but these values are slightly higher than the spontaneous beating rate for adult cells [27,63,69]. However, these results should be confirmed with paced cells to assess the effect of pacing on cytoskeletal organization and maturation, as well as on the contractile properties of these cells.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Furthermore, we found that the average beat frequency of hiPSC-CMs on microposts coated with all three ECM proteins was approximately equal, and only varied from 0.9 to 1.1 Hz. These findings agree with previous measurements of the spontaneous beating rate for early-stage iPSC-derived cardiomyocytes, but these values are slightly higher than the spontaneous beating rate for adult cells [27,63,69]. However, these results should be confirmed with paced cells to assess the effect of pacing on cytoskeletal organization and maturation, as well as on the contractile properties of these cells.…”
Section: Discussionsupporting
confidence: 91%
“…The average twitch velocity of early-stage (20-40 days postdifferentiation) hiPSC-derived cardiomyocytes has previously been measured to be approximately 2 lm/s, based on optical edge detection, while the twitch velocity of midstage (40-60 days postdifferentiation) cells was approximately 3 lm/s [69]. Alternatively, using traction force microcopy, the average twitch velocity of midstage hESC-derived cardiomyocytes on a 4 kPa gel was measured to be approximately 6.9 lm/s [62].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Shinozawa et al used in vitro aging to show that, while day-30 cardiomyocytes already demonstrate basic electrophysiological properties, day-60 and -90 cardiomyocytes have more mature morphological and functional traits. 36 On the other hand, 3D topology has been shown to influence cell morphology, cellular junctions, and myofibril protein expression. 37 …”
mentioning
confidence: 99%
“…The electrophysiological properties and force of contraction vary significantly from adult cardiomyocytes, raising questions on the validity of the drug response observed using hPSC-CM [12,25]. While a 2D monolayer of hPSC-CM expresses most of the ion channels that are of interest for drug screening [15], hPSC-CM change ion channel expression levels and develop subcellular structures such as sarcoplasmic reticulum over long culture periods (~100 days) [2628]. The concern over hPSC-CM immaturity has further contributed to the development of microphysiological systems, as many strategies to mature hPSC-CM involve mimicking the native cardiac microenvironment, as recently reviewed [29].…”
Section: Two-dimensional Modelsmentioning
confidence: 99%